2018
DOI: 10.1158/1078-0432.ccr-17-1776
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin Is Required for Lung Adenocarcinoma Metastasis via Heterotypic Tumor Cell–Cancer-Associated Fibroblast Interactions during Collective Invasion

Abstract: Purpose: Vimentin is an epithelial-to-mesenchymal transition (EMT) biomarker and intermediate filament protein that functions during cell migration to maintain structure and motility. Despite the abundance of clinical data linking vimentin to poor patient outcome, it is unclear if vimentin is required for metastasis or is a correlative biomarker. We developed a novel genetically engineered mouse model (GEMM) to probe vimentin in lung adenocarcinoma metastasis.Experimental Design: We used the LSL- CIPs correlat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
141
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(156 citation statements)
references
References 48 publications
13
141
0
2
Order By: Relevance
“…As reported, depletion of N-cadherin suppressed cell invasion and migration in LUAD [29]. As a biomarker of EMT, Vimentin is an intermediate filament protein that plays a role in cell migration to keep structure and motility [30]. Through maintaining heterotypic cancer cell-cancer-associated fibroblast interactions during collective invasion, Vimentin was required for LUAD metastasis [30].…”
Section: Discussionmentioning
confidence: 78%
“…As reported, depletion of N-cadherin suppressed cell invasion and migration in LUAD [29]. As a biomarker of EMT, Vimentin is an intermediate filament protein that plays a role in cell migration to keep structure and motility [30]. Through maintaining heterotypic cancer cell-cancer-associated fibroblast interactions during collective invasion, Vimentin was required for LUAD metastasis [30].…”
Section: Discussionmentioning
confidence: 78%
“…In 3D in vitro invasion assays, the addition of CAFs to lung adenocarcinoma cell line spheroids increased spheroid branching. The knock-down of vimentin in CAFs decreased this effect, meaning that the presence of CAFs with intact vimentin led to effective collective migration [97]. This highlights the importance of vimentin in other cell types associated with tumors and metastases and the variety of roles vimentin plays in metastasis formation.…”
Section: Research Focused On Vimentin In Metastasesmentioning
confidence: 83%
“…However, many recent studies have shown that EMT activation is detrimental to the dissemination and invasion of certain cancer cells . During EMT, epithelial tumor cells lose their epithelial traits, such as E‐cadherin expression, and instead display mesenchymal traits, such as vimentin expression . E‐cadherin is considered to be an active suppressor of the invasion and growth of many epithelial cancers, while higher expression of claudin‐1 is a good prognostic factor in NSCLC, but only in the SCC subgroup .…”
Section: Discussionmentioning
confidence: 99%